Effect of drying and grinding characteristics of colored potato (Solanum tuberosum L.) on tribology of mashed colored potato paste - Hyeon Woo Park; Won Byong Yoon (CyTA - Journal of Food, 2018)
The mouthfeel of mashed potato prepared with steamed purple flesh potato (SPFP) was investigated by measuring tribological and rheological characteristics. Mathematical models describing pre-processes such as drying and grinding associated with physical properties of mashed potato were also explored. The effect of drying temperature (60, 70, 80, and 90°C) on quality changes (moisture and anthocyanin content) of SPFP was successfully described (R2 > 0.9583). The sigmoid model was suitably applied to estimate particle sizes of dried SPFP during grinding (R2 > 0.9864). As the particle size of mashed SPFP increased, friction coefficient increased, and storage and loss modulus decreased. Taste, smoothness, and after-feel sensation were increased as particle sizes decreased, while appearance and odor showed no significant differences. To predict the sensory property using tribology and rheology, the specific conditions were successfully determined (R2 > 0.9926).